2012
DOI: 10.1123/jsr.21.4.371
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Injury-Prevention Programs in Reducing the Incidence of Anterior Cruciate Ligament Sprains in Adolescent Athletes

Abstract: Clinical Scenario: There is a high incidence of anterior cruciate ligament (ACL) injury in adolescents participating in pivoting sports such as soccer, basketball, and handball. Most ACL injuries in athletes are noncontact injuries, with a mechanism of sudden deceleration, change in direction, or landing from a jump. These mechanisms coupled with an increase in contraction of the quadriceps have been shown as risk factors for ACL injuries. Injuries to the ACL may require surgery, a long rehabilitation, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
0
13
0
2
Order By: Relevance
“…Irrespective of the intervention practitioners should ensure the coaching and progression of exercise is sufficient to continue to drive adaptations (44). To promote compliance we recommend a focus upon the education of coaches (24) and players to the potential benefits from both an injury prevention and physical performance enhancement perspective, as the latter may increase player motivation (1).…”
Section: Considerations For Planning and Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Irrespective of the intervention practitioners should ensure the coaching and progression of exercise is sufficient to continue to drive adaptations (44). To promote compliance we recommend a focus upon the education of coaches (24) and players to the potential benefits from both an injury prevention and physical performance enhancement perspective, as the latter may increase player motivation (1).…”
Section: Considerations For Planning and Deliverymentioning
confidence: 99%
“…This is evident in the compliance of female soccer players to neuromuscular training programs which can improve physical performance (15,43,45) and reduce injury risk factors (12,44,50,51,57,59) when implemented successfully. Studies, however, often report poor compliance with the training intervention (1, 12,44,59) or poor intervention fidelity (29). For example one study demonstrated neuromuscular training improved star excursion balance score yet 31% of players had to be excluded as they did not comply with the intervention (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most non-contact ACL injuries occur during sudden deceleration, rapid change of direction, or while landing from a jump (Paszkewicz et al, 2012). It is under these dynamic conditions, and in particular within the first 30 to 50 ms after initial ground contact (Koga et al, 2010), that the ACL appears to be most vulnerable to injury from a biomechanical perspective.…”
Section: Introductionmentioning
confidence: 99%
“…These showed a hip and knee control de icit during jump-landing and a lack of postural stability. extremities and trunk among subjects (mainly female) with a risk of ACL rupture, prevention programs were adopted and integrated into physical preparation and training for different sports 19,20 .…”
Section: Proprioceptive Controlmentioning
confidence: 99%